Lily's crossing - Giff, Patricia Reilly (New York A Yearling Book, 1997)
During a summer spent at Rockaway Beach in 1944, Lily's friendship with a young Hungarian refugee causes her to see the war and her own world differently.
Keywords: World War, 1939-1945 -- United States -- Juvenile fiction; Large type books; World War, 1939-1945 -- United States -- Fiction; Friendship -- Fiction; Refugees -- Fiction; Beaches -- Fiction; Large type books